2023
DOI: 10.1155/2023/5569262
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Protozoan Parasitosis and Associated Factors among Patients with and without Diabetes Mellitus in a Teaching Hospital in Ghana

Eric Konadu,
Mainprice Akuoko Essuman,
Angela Amponsah
et al.

Abstract: Background. Enteric protozoa infections (EPIs) could worsen clinical outcomes in patients with diabetes mellitus and therefore requires prompt and accurate diagnosis and attention. This study aimed to determine the burden of EPIs and their associated factors among patients with and without diabetics at the Komfo Anokye Teaching Hospital (KATH) in Ghana. Again, the diagnostic performance of parasitological techniques routinely used for diagnosis was assessed. Methods. A total of 240 participants (made up of 140… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…Case-control studies carried out in Lybia and Ghana indicated a higher prevalence of Cryptosporidium spp., C. belli, and D. fragilis among diabetic patients compared to notdiabetic controls, most probably for the reduced activity of phagocytes and cytokine production resulting from chronic inflammation in diabetes [65,66]. Coinfection with different parasites was more frequent in diabetic patients [65].…”
Section: Parasitic Protozoans In Immunocompromised Patientsmentioning
confidence: 98%
“…Case-control studies carried out in Lybia and Ghana indicated a higher prevalence of Cryptosporidium spp., C. belli, and D. fragilis among diabetic patients compared to notdiabetic controls, most probably for the reduced activity of phagocytes and cytokine production resulting from chronic inflammation in diabetes [65,66]. Coinfection with different parasites was more frequent in diabetic patients [65].…”
Section: Parasitic Protozoans In Immunocompromised Patientsmentioning
confidence: 98%